1970
DOI: 10.1021/jf60167a039
|View full text |Cite
|
Sign up to set email alerts
|

Dieldrin-14C metabolism in sheep. Distribution and isolation of urinary metabolites

Abstract: Seven sheep were given 165 to 230 microcuries of dieldrin-14C. Three to 14% of the radioactive dose was recovered in the urine over 3-to 6-day periods. This radioactivity was contained in six metabolites, four of which were extracted from urine with hexane and two of which were not. The extraction and isolation of these metabolites are described.That chlorinated hydrocarbon insecticides, such as dieldrin, are accumulated in body fat is well known. However, only recently has the metabolism of dieldrin and relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1970
1970
1980
1980

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 5 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…Equal amounts of excretion in feces of orally and intraperitoneally treated rats were also observed at the end of a 12-week period (Dailey et al, 1970). Higher levels of excretion of orally administered dieldrin through feces were also observed in rats (Matthews et al, 1971), sheep (Hedde et al, 1970), and cows (Wilson and Cook, 1972). a Free, 14C radioactivity extracted with ethyl acetate; acid released, radioactivity extracted with ethyl acetate from the aqueous phase and extracted tissues after treatment with 1 N HC1; water soluble, radioactivity remaining in water phase after acid treatment and ethyl acetate extraction; solids, radioactivity unextractable from the solids after acid treatment and ethyl acetate extraction.…”
Section: Discussionmentioning
confidence: 82%
“…Equal amounts of excretion in feces of orally and intraperitoneally treated rats were also observed at the end of a 12-week period (Dailey et al, 1970). Higher levels of excretion of orally administered dieldrin through feces were also observed in rats (Matthews et al, 1971), sheep (Hedde et al, 1970), and cows (Wilson and Cook, 1972). a Free, 14C radioactivity extracted with ethyl acetate; acid released, radioactivity extracted with ethyl acetate from the aqueous phase and extracted tissues after treatment with 1 N HC1; water soluble, radioactivity remaining in water phase after acid treatment and ethyl acetate extraction; solids, radioactivity unextractable from the solids after acid treatment and ethyl acetate extraction.…”
Section: Discussionmentioning
confidence: 82%
“…Twenty-four hours before slaughter, all sheep being fed 2 mg dieldrin per kg were put in metabolism cages (Hedde et al, 1970) and given 50 to 100 µ dieldrin-14C, specific activity 25 to 190 gCi per mg. Urine and feces were collected, and after slaughter, feces, tissues, and carcasses were handled as above.…”
Section: Methodsmentioning
confidence: 99%
“…Assay procedures for dieldrin-14C in tissues and excretions were those described by Hedde et al (1970).…”
Section: Methodsmentioning
confidence: 99%
“…Results of other experiments of dieldrin metabolism, storage and elimination indicated that dieldrin is stored in body tissues predominantly as dieldrin and that metabolites of dieldrin predominate in urine and feces (Davison 1970, Hedde et al 1970, Feil et al 1970, Davison and Sell 1978. Therefore, it was assumed for these experiments that radioactive measurements based on carbon-14 would be a good indicator of the amount of dieldrin stored in the chicken carcasses and also would be a good indicator of the elimination of dieldrin from body stores, without regard to whether dieldrin was metabolized during the elimination process.…”
Section: Resultsmentioning
confidence: 99%